Analisis Peran Badan Usaha Milik Desa (BUMDes) Terhadap Peningkatan Kesejahteraan Masyarakat Di Desa Wisata Kembang Kuning, Kecamatan Sikur, Lombok Timur. - Nurhayati, Nurhayati (Lembaga Riset Ilmiah, 2022)
Village-Owned Enterprises (BUMDes) are business institutions managed by the community and village government in an effort to strengthen the village economy and build community social cohesion which is formed based on the needs and potential of the village. Community welfare is a condition that shows the state of people's lives which can be seen from the standard of living of the community. This study aims to determine the steps taken by BUMDes in improving the community's economy and the economic benefits felt by the community with the presence of BUMDes in Kembang kuning village. The research method used in this study is a descriptive approach with a naturalistic or qualitative approach. The data collection technique was in the form of observation consisting of in-depth interviews and documentation. The results of this study indicate that the management of BUMDes to improve welfare has not shown welfare to the community, because the data from 2017 to 2021 show a decline in the tourism sector which is deserted by tourists and a decrease in BUMDes finances which causes limited capital turnover. The BUMDes products offered are very helpful for the community in fulfilling their needs as an economic benefit but have not provided welfare to the community. Supporting factors in the management of BUMDes are tourism potential and increased resources to improve the performance of BUMDes managers in providing welfare to the community of Kembang kuning village.